Sister Mary Joseph's nodule in a patient with metastatic small cell lung cancer - Sushil Ghimire; Smith Giri; Ranjan Pathak; Mike G Martin (Greater Baltimore Medical Center, 2015)
We present a case of 56-year-old male with small cell carcinoma of the lung with metastatic tumor nodule of the umbilicus. To our knowledge, this is only the second reported case of small cell lung cancer associated with Sister Mary Joseph's nodule.